Efficient solar-driven electrochemical CO2 reduction to hydrocarbons and oxygenates. Issue 10 (15th September 2017) - Gurudayal,; Bullock, James; Srankó, Dávid F.; Towle, Clarissa M.; Lum, Yanwei; Hettick, Mark; Scott, M. C.; Javey, Ali; Ager, Joel
Abstract : In a process analogous to natural photosynthesis, solar-driven reduction of carbon dioxide to hydrocarbon and oxygenate products is demonstrated with an overall efficiency exceeding 5%. Abstract : Solar to chemical energy conversion could provide an alternative to mankind's unsustainable use of fossil fuels. One promising approach is the electrochemical reduction of CO2 into chemical products, in particular hydrocarbons and oxygenates which are formed by multi-electron transfer reactions. Here, a nanostructured Cu–Ag bimetallic cathode is utilized to selectively and efficiently facilitate these reactions. When operated in an electrolysis cell, the cathode provides a constant energetic efficiency for hydrocarbon and oxygenate production. As a result, when coupled to Si photovoltaic cells, solar conversion efficiencies of 3–4% to the target products are achieved for 0.35 to 1 Sun illumination. Use of a four-terminal III–V/Si tandem solar cell configuration yields a conversion efficiency to hydrocarbons and oxygenates exceeding 5% at 1 Sun illumination. This study provides a clear framework for the future advancement of efficient solar-driven CO2 reduction devices.